THE APPLICATION OF FUNGICIDES AND GROWTH REGULATORS FOR SEEDBED TREATMENT OF SPRING WHEAT SEEDS IN THE IRKUTSK REGION - A. A. Razina; О. G. Dyatlova (Зерновое хозяйство России, 2018)
The purpose of the present study was to identify the biological and economic efficiency of fungicides ‘Maksim Plus’ (1.2 l/t), ‘BisolbiSan’ (1l/t) and the plant growth regulator ‘Melafen’ (10 ml/t) in the pre-treatment of spring wheat seeds in pure form and in tank mixtures.The investigations were carried out in the experimental field rotation. The technology of cultivation was zonal, the forecrop was peas, the spring awny wheat variety ‘Buryatskaya’ was experimented. In all variants of the trial, the pre-treatment of the seeds was conducted with watering (10 litersof water per 1 ton of seeds) 10 days prior to sowing process. It has been established that the use of fungicides ‘Maksim Plus’ and ‘BisolbiSan’ and plant growth regulator ‘Melafen’ in its pure form is not sufficient to reveal spring wheat potential in seed pre-treatment, despite better plant growth and development characteristics, decrease of seed infection and root rot, compared with the control variety, because the obtained yield increase proved to be unreliable. Seed pre-treatment with the tank mixtures ‘Maksim Plus+ Melafen’, ‘Maksim Plus + BisolbiSan’ is agronomically justified, as it had a significant effect on average suppression of seed infection (by 74%) and root rot in the germination period (31.4–32.8%), it increased plants’ resistance to root rot pathogens, which resulted in reliable improvement of grain productivity: on 0.74 and 0.60 t/ha on average, respectively. The costs are paid off by the increased crop yields. In 2016 profitability of the combination of chemical disinfectant ‘Maksim Plus’ with growth regulator ‘Melafen’ and fungicide ‘BisolbiSan’ was 68.3 and 88.2%, respectively. In 2017, the use of fungicide ‘Maksim Plus’ and ‘Melafen’ ensured 36% profitability of wheat grain production and 53% with ‘BisolbiSan’.